Factors and Coping Styles Related to Breast Cancer Patients’ Preferences About Referrals to Psychotherapy as part of Treatment: Factors and coping styles related to BC - Counselman-Carpenter, Elisabeth; Williams, Joyce (Archives of Breast Cancer, 2024)
Background: The purpose of this mixed methods study was to examine what factors may influence emotional suppression and emotional expression in breast cancer patients and how coping styles relate to beliefs about physician-driven referrals to therapy. Methods: A mixed method research design consisting of quantitative methods including a demographics survey, the Courtald Emotional Control Scale and treatment preference questionnaires followed by optional participation in a semi-structured interview. Results: Demographic variables including age, marital status, income, and experience of psychotherapy prior to breast cancer diagnosis are statically significant factors that influence CECS scores and coping styles. Participants universally believed that there should be some level of psychotherapy referrals for supportive mental health care during and after the treatment process. Conclusion: Participants who fell into either category of emotional suppressor or emotional expresser believed that there should be physician driven referrals to therapy during the breast cancer treatment process. Both those identified as suppressors and expressers indicated high rates of concealing one’s true emotional experience. This highlights the need for psychological therapy referrals to be integrated as a best practice, regardless of patient’s identified coping style or demographic identities. We suggest that all breast cancer patients be screened at multiple points and offered a referral by every member of their treatment team: regardless of how they seem to cope and that future research focus on the most efficient and holistic ways to decrease barriers to receiving psychological support during and after breast cancer treatment.